Brighter Days May Be Ahead: Continuous Measurement of Pediatric Intensive Care Unit Light and Sound - Greenfield, Kara D.; Karam, Oliver; Iqbal O'Meara, A. M. (Frontiers in Pediatrics, 2020)
Objective: To describe light and sound characteristics in the rooms of critically ill children. Design: Prospective observational cohort study, with continuously measured light and sound levels. Setting: Tertiary care pediatric intensive care unit (PICU), with a newly constructed expansion and an older, pre-existing section. Patients: Critically ill patients 0-18 years old, requiring respiratory or cardiovascular support. Patients with severe cognitive preconditions were excluded. Measurements and Main Results: 100 patients were enrolled, totaling 602 patient-days. The twenty-four hour median illuminance was 16 (IQR 5-53) lux (lx). Daytime (07:00-21:00) median light level was 27 lx (IQR 13-82), compared with 4 lx (IQR 1-10) overnight (22:00-06:00). Peak light levels occurred midday between 11:00-14:00, with a median of 48 lx (IQR 24-119). Daytime median illuminance trended higher over the course of admission, whereas light levels overnight were consistent. Midday light levels were higher in newly constructed rooms: 78 lx (IQR 30-143) versus 26 lx (IQR 20-40) in existing rooms. The twenty-four hour median equivalent sound level (LAeq) was 60 (IQR 55-64) decibels (dB). Median daytime LAeq was 62 dB (IQR 58-65) and 56 dB (IQR 52-61) overnight. On average, 35% of patients experienced at least one sound peak >80 dB every hour from 22:00-06:00. Overnight peaks, but not median sound levels nor daytime peaks, decreased over the course of admission. There was no difference in sound between new and pre-existing rooms. Conclusions: This study describes continuously measured light and sound in PICU rooms. Light levels were low even during daytime hours, while sound levels were consistently higher than World Health Organization hospital room recommendations of <35 dB. Given the relevance of light and sound to sleep/wake patterns, and evidence of post-intensive care syndromes, the clinical effects of light and sound on critically ill children should be further explored as potentially modifiable environmental factors.